An effective and simple procedure to isolate abundant quantities of biologically active chemopreventive Lunasin Protease Inhibitor Concentrate (LPIC) from soybean. (15th June 2015) - Krishnan, Hari B.; Wang, Thomas T.Y.
Highlights: A novel method for isolation of Lunasin and Protease Inhibitors. Procedure is based on ethanol extraction and preferential precipitation with calcium. Yields 3.2 g of Lunasin Protease Inhibitor Concentrate (LPIC) from 100 g of soybean flour. Potential to scale up to yield kilograms of highly enriched lunasin preparations. LPIC shown to inhibit overproduction of pro-inflammatory cytokines. Abstract: Lunasin is a 5-kDa soybean bioactive peptide with demonstrated anti-cancer and anti-inflammatory properties. Recently, purification methods have been developed to obtain gram quantities of lunasin. However, these methods are cumbersome, time consuming and cost-prohibitive. To overcome these constrains we have developed a novel method which involves extraction of soybean flour with 30% ethanol followed by preferential precipitation of lunasin and protease inhibitors by calcium. The calcium precipitated protein fraction, which we termed as Lunasin Protease Inhibitor Concentrate (LPIC), contains three abundant proteins with molecular weights of 21, 14 and 5 kDa. This simple procedure yields 3.2 g of LPIC from 100 g of soybean flour and the entire isolation procedure can be completed in less than 2 h. Treatment of THP-1 human monocyte cell lines with LPIC resulted in suppression of lipopolysaccharide-stimulated cytokine expression, demonstrating that the LPIC isolated by our simple procedure is biologically active.